Sustainable chemo-enzymatic synthesis of glycerol carbonate (meth)acrylate from glycidol and carbon dioxide enabled by ionic liquid technologies. Issue 11 (21st May 2021) - Villa, Rocio; Porcar, Raul; Nieto, Susana; Donaire, Antonio; Garcia-Verdugo, Eduardo; Luis, Santiago V.; Lozano, Pedro
Abstract : A sustainable chemo-enzymatic process for producing both glycerol carbonate acrylate and glycerol carbonate methacrylate, as monomers for the preparation of biodegradable plastic materials, has been developed by using ionic liquid technologies. Abstract : A sustainable chemo-enzymatic process for producing both glycerol carbonate acrylate (GCA) and glycerol carbonate methacrylate (GCMA), as useful monomers for the preparation of biodegradable plastic materials, has been carried out by taking advantage of ionic liquid (IL) technologies. The process consisted of two consecutive catalytic steps, which can be carried out by either sequential or one-pot experimental approaches. Glycidyl (meth)acrylate was firstly synthesized by enzymatic transesterification of (meth)acrylate vinyl ester with glycidol in Sponge Like Ionic Liquids (SLILs) as the reaction medium (100% yield after 6 h at 60 °C). SLILs not only provided a suitable reaction medium, but also allowed the simple isolation of the resulting glycidyl esters as an IL-free pure fraction through a straightforward cooling/centrifugation protocol. The second step consisted of the synthesis of GCA, or GCMA, as the outcome of the cycloaddition of CO2 to the obtained glycidyl acrylate or glycidyl methacrylate, respectively, catalysed by a covalently attached 1-decyl-2-methylimidazolium moiety (Supported Ionic Liquid-Like Phase, SILLP) in a solvent-free system and under mild conditions (60 °C, 1–10 bar), leading to up to 100% yield after 6 h. The components of the reaction system (biocatalyst/SLIL/SILLP) can be fully recovered and reused for at least 6 cycles with unchanged catalytic performance.